Evaluation of reservoirs in bleaching trays for at-home bleaching: a split-mouth single-blind randomized controlled equivalence trial (Journal of Applied Oral Science, 2021)
Objectives: This randomized, split-mouth, single-blinded trial assessed whether the use of reservoirs in at-home bleaching trays is equivalent to non-reservoir trays. Our choice of an equivalence trial was based on the expectation that a non-reservoir tray is sufficient to produce a color change. Secondary outcomes such as tooth sensitivity (TS) and gingival irritation (GI) were also assessed. Methodology: Forty-six patients were selected with canines shade A2 or darker. In half of the patient’s arch, bleaching trays were made with reservoirs and the other half, without reservoirs. At-home bleaching was performed with carbamide peroxide (CP) 10% (3 h daily; 21 days). Color change was evaluated with a digital spectrophotometer (ΔE, ΔE00, and Whiteness Index) and shade guide units (ΔSGU) at baseline, during and one-month post-bleaching. TS and GI were assessed with a numeric scale (NRS) and a visual analog scale (VAS). Results: After one month, the equivalence of reservoir and non-reservoir groups were observed in all color instruments (p>0.05). Fifteen and sixteen patients presented pain (absolute risk: 33% and 35%, 95%, confidence interval (CI) 21-46% and 23-49%) in the reservoir and non-reservoir side, respectively. The odds ratio for pain was 0.8 (95%CI 0.2-3.0) and the p-value was non-significant (p=1.0). TS intensity was similar between both groups in any of the pain scales (p>0.05). No difference in the GI was observed (p>0.05). Conclusions: The protocol with reservoirs is equivalent in color change to the non-reservoir, although no superiority of the latter was observed in terms of reduced TS and GI with at-home 10% carbamide peroxide bleaching. Clinical Relevance: The presence of reservoirs in a bleaching tray did not improve color change or affect tooth sensitivity and gingival irritation.